SIMMEON‐Prep study: SIMulation of Medication Errors in ONcology: prevention of antineoplastic preparation errors. (18th October 2014) - Sarfati, L.; Ranchon, F.; Vantard, N.; Schwiertz, V.; Gauthier, N.; He, S.; Kiouris, E.; Gourc‐Berthod, C.; Guédat, M. G.; Alloux, C.; Gustin, M.‐P.; You, B.; et al.
Summary What is known and objective Medication errors (ME) in oncology are known to cause serious iatrogenic complications. However, MEs still occur at each step in the anticancer chemotherapy process, particularly when injections are prepared in the hospital pharmacy. This study assessed whether a ME simulation program would help prevent ME‐associated iatrogenic complications. Methods The 5‐month prospective study, consisting of three phases, was undertaken in the centralized pharmaceutical unit of a university hospital of Lyon, France. During the first simulation phase, 25 instruction sheets each containing one simulated error were inserted among various instruction sheets issued to blinded technicians. The second phase consisted of activity aimed at raising pharmacy technicians' awareness of risk of medication errors associated with antineoplastic drugs. The third phase consisted of re‐enacting the error simulation process 3 months after the awareness campaign. The rate and severity of undetected medication errors were measured during the two simulation (first and third) phases. The potential seriousness of the ME was assessed using the NCC MERP® index. Results and discussion The rate of undetected medication errors decreased from 12 in the first simulation phase (48%) to five in the second simulation phase (20%, P = 0∙04). The number of potential deaths due to administration of a faulty preparation decreased from three to zero. Awareness of iatrogenic risk through error simulation allowed pharmacy technicians to improve their ability to identify errors. What is new and conclusion This study is the first demonstration of the successful application of a simulation‐based learning tool for reducing errors in the preparation of injectable anticancer drugs. Such a program should form part of the continuous quality improvement of risk management strategies for cancer patients.